Aerodynamics effect of computational fluid dynamics approach on different propeller blade design subjected to origin position - Ahmad Faris, Ahmad Fariduddin (2021)
The current work presents a numerical method investigation of small-scale propeller aerodynamics performance on 4 different shapes of propeller design using Computational Fluid Dynamic (CFD). This study is conducted due to less studies has been conducted in this airfoil’s origin position (AOP) in CFD study, limited study was conducted on the aerodynamics performance respected to the change of origin blade position. In this study, the relationship between the changing of each AOP at each station and the aerodynamics performance was investigated using the CFD approach. The propellers were designed by changing the AOP at each blade station which produced a different design of propeller shape which can be referred to in percentage of 0% AOP, 25% AOP, 50% AOP, 75% AOP, and 100% AOP. Finite Volume Method using ANSYS Fluent 18.2 was used to analyse this analyses. Multiple Reference Frame (MRF) technique was used for the rotation of the propeller subjected to its local reference frame at 3008 revolutions per minute (RPM). The result of thrust, power coefficients and efficiencies were successfully validated with the experimental wind tunnel data and further the study was conducted to analyse the aerodynamics effect of the 4 different propellers design. The 100% AOP generates an improvement in aerodynamics performance in terms of thrust, coefficient of power, and efficiency with 7.473%, -5.587%, and 15.891% with respect to 25% AOP. The results also showed a better aerodynamics performance compared to the 25% AOP, 50% AOP, and 75% AOP, especially at the advance ratio of 0.799. This has proven that by increasing the position of the blade origin at each station which develop different of propeller design shape has improved the aerodynamic characteristic and performance of the propeller blade. Hence, using the novel technique of CFD analysis can provide a better platform in designing the best aerodynamics propeller blade design before fabricating the actual model of a propeller.